2009
DOI: 10.1542/peds.2008-2233c
|View full text |Cite
|
Sign up to set email alerts
|

Status of Childhood Asthma in the United States, 1980–2007

Abstract: Centers for Disease Control and Prevention data were used to describe 1980 -2007 trends among children 0 to 17 years of age and recent patterns according to gender, race, and age. Asthma period prevalence increased by 4.6% per year from 1980 to 1996. New measures introduced in 1997 show a plateau at historically high levels; 9.1% of US children (6.7 million) currently had asthma in 2007. Ambulatory care visit rates fluctuated during the 1990s, whereas emergency department visits and hospitalization rates decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
727
5
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 940 publications
(752 citation statements)
references
References 50 publications
15
727
5
5
Order By: Relevance
“…In the United States, data from the Centers for Disease Control and Prevention pointed to an increase of 4.6% from 1980 to 1996 and a stability in the prevalence of asthma in individuals aged between zero and 17 years, between 1997 and 2007. 1 By analyzing information from all countries that participated in the ISAAC, Pearce et al 15 observed an annual increase in asthma prevalence in adolescents that varied between 0.07% in Africa and 0.93% in Oceania. Only in the Indian subcontinent was there an annual decrease of 0.01%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, data from the Centers for Disease Control and Prevention pointed to an increase of 4.6% from 1980 to 1996 and a stability in the prevalence of asthma in individuals aged between zero and 17 years, between 1997 and 2007. 1 By analyzing information from all countries that participated in the ISAAC, Pearce et al 15 observed an annual increase in asthma prevalence in adolescents that varied between 0.07% in Africa and 0.93% in Oceania. Only in the Indian subcontinent was there an annual decrease of 0.01%.…”
Section: Discussionmentioning
confidence: 99%
“…prevalence of asthma in childhood, with a reduction in mortality rates in the same period. 1 A study conducted by Pearce et al, 15 with data from the International Study of Asthma and Allergy in Childhood (ISAAC), showed a reduction in asthma in English-speaking countries and Western Europe. In contrast, there was an increase in the asthma prevalence throughout the years in countries where the prevalence was considered to be low.…”
Section: Introductionmentioning
confidence: 99%
“…asthma. For example, 402 wheezing is known as a primary symptom of asthma in early childhood 25 and 403 about 40% of childhood wheeze will persist later in life and will eventually 404 develop into asthma by 6 years of age 26 , indicating majority of wheeze during 405 infancy are in fact acute respiratory infection. Therefore, extended follow-up of 406 these trials could help to provide a clearer answer as to whether the vitamin D 407 intervention is beneficial for asthma prevention.…”
mentioning
confidence: 99%
“…[27] In 2006 in the USA, 155 000 children were admitted for asthma and contributed 5.6% of all admitted children; there were also 593 000 emergency room visits of children for asthma, contributing 2.3% of all paediatric emergency room visits. [28] The numbers of admissions and visits were highest among the youngest patients and decreased with advancing age, although the prevalence of asthma was higher in school-age children and adolescents. [28] A hospital discharge survey performed in the USA in 2005 showed that 45% of neonates had at least one illness or risk-related diagnosis.…”
Section: /25mentioning
confidence: 96%
“…[28] The numbers of admissions and visits were highest among the youngest patients and decreased with advancing age, although the prevalence of asthma was higher in school-age children and adolescents. [28] A hospital discharge survey performed in the USA in 2005 showed that 45% of neonates had at least one illness or risk-related diagnosis. [29] Common diagnoses were perinatal jaundice (20%), respiratory conditions (11%), disorders related to prematurity (8%), and congenital anomalies (8%).…”
Section: /25mentioning
confidence: 96%